2021
DOI: 10.52082/jssm.2021.339
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Evidence for Non-Local Muscle Fatigue and Performance Enhancement in Young Adults

Abstract: Post-activation performance enhancement (PAPE) is an improvement to voluntary muscle performance following a conditioning activity. There is evidence of fatigue resistance deficits in non-exercised muscles following unilateral fatiguing exercise of a contralateral muscle. The purpose of this study was to determine if a unilateral conditioning exercise protocol could induce PAPE in a contralateral, non-exercised muscle in young healthy adults. Thirty-two recreationally trained (n = 16) and athletically trained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…In this case, the PAPE effect of the whole muscle chain was neglected. Power et al (28) found no significant drop jump performance or EMG activity difference when the tested leg did or did not undergo the activation. On the contrary, Neltner et al (27) found the result of nonlocalized potentiation of the contralateral nonexercising leg, whose peak torque (PT) increased from the prevalue (167 ± 34 Nm) to the post-value (173 ± 32 Nm) after the fatiguing protocol of the opposite leg.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the PAPE effect of the whole muscle chain was neglected. Power et al (28) found no significant drop jump performance or EMG activity difference when the tested leg did or did not undergo the activation. On the contrary, Neltner et al (27) found the result of nonlocalized potentiation of the contralateral nonexercising leg, whose peak torque (PT) increased from the prevalue (167 ± 34 Nm) to the post-value (173 ± 32 Nm) after the fatiguing protocol of the opposite leg.…”
Section: Introductionmentioning
confidence: 99%